Chile - Martinez, Renee Russo; Shan, Leong Wen (Milwaukee, Wis. : Gareth Stevens Pub., 2003)
Provides an overview of the geography, history, government, people, arts, foods, and other aspects of life in Chile.
Includes bibliographical references (p. 94) and index.
Keywords: Chile -- Juvenile literature; Chile